Badania, herstoria i praca kobiet — od PRL do dziś. Szkic do historii socjologii pracy kobiet - Desperak, Iza; Krogulec, Martyna (Górnośląskie Studia Socjologiczne. Seria Nowa, 2020)
The article intends to sketch history of sociology of women’s work, and focuses on transition between the Polish People’s Republic and contemporary Poland. It describes main patterns of development of study on women at work, with its peak in the 1960s and 1970s, than marginalization of this subject, and its revival in transition period. The analysis is supported by the first results of Łódź multidisciplinary research project aiming to describe history of women’s work and research on it conducted by the University of Łódź and the Institute of Occupational Medicine. It also includes new research conducted by historians, and its multidisciplinary character is supported by some non-academic participants of the project, including museums and local herstory movement. Łódź has been chosen for its long tradition of feminization of workforce, and great bulk of research on working women, both in the past and during transition period, including new phenomena of unemployment, then feminization of poverty and precarious character of today’s work affecting also women.